A questão da reflexão e da ação nas práticas psicoeducativas na pesquisa interventiva - Calil, Simone Dalla Barba Walckoff (2009)
This phenomenological study investigated three psychoeducational practices which were developed and utilised in an interventionist research work conducted in a community by PUC-SP s ECOFAM (Research Team in Educational Practice and Psychoeducational Attention to Families, Schools and Communities, Postgraduate Programme in Educational Psychology, Catholic University of Sao Paulo). The author carried out an analysis of the procedures adopted between 2004 and 2006. Her aim was to understand how the psychoeducational practices were put into effect and what contributions they made to their participants. This was done in the light of their ability to prompt action, as seen in terms of Hannah Arendt s work. The analysis was based on hermeneutics and on the ideas proposed by Arendt. It suggests that there is a need to relativise thought in what concerns the aim of an intervention in a community, this aim being, according to Arendt, the beginnning of a new movement. It also identifies several aspects related to the issue of action, such as volition, judgement, power, plurality, and conditioning. It thus highlights the importance of the fact that an intervention should take on board these different aspects as a way of increasing its effectiveness